2023
DOI: 10.1002/ags3.12662
|View full text |Cite
|
Sign up to set email alerts
|

Annual report on National Clinical Database 2020 for gastroenterological surgery in Japan

Abstract: Aim The National Clinical Database (NCD) of Japan is a nationwide data entry system for surgery, and it marked its 10th anniversary in 2020. The aim was to present the 2020 annual report of gastroenterological surgery of the NCD. Methods The data of the surgical procedures stipulated by the training curriculum for board‐certified surgeons of the Japanese Society of Gastroenterological Surgery in the NCD from 2011 to 2020 were summarized. Results … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
29
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 43 publications
0
29
0
Order By: Relevance
“…Recently, Yoshida et al 52 reported excellent results of low anastomotic leakage rate (0.67%) and incidence of pneumonia (3.0%) via the subtotal stomach approach. The rate of anastomotic leakage and incidence of pneumonia were both lower than those reported in NCD data in Japan 10,52 . The subtotal stomach approach has also been reported to maintain good QOL with less postoperative reflux.…”
Section: Shape and Size Of The Gastric Conduitmentioning
confidence: 63%
See 4 more Smart Citations
“…Recently, Yoshida et al 52 reported excellent results of low anastomotic leakage rate (0.67%) and incidence of pneumonia (3.0%) via the subtotal stomach approach. The rate of anastomotic leakage and incidence of pneumonia were both lower than those reported in NCD data in Japan 10,52 . The subtotal stomach approach has also been reported to maintain good QOL with less postoperative reflux.…”
Section: Shape and Size Of The Gastric Conduitmentioning
confidence: 63%
“…NCD revealed a decreasing trend in mortality rate for esophagectomy from 3.2% in 2011 to 1.5% in 2020, which is similar to the mortality rate for total gastrectomy. 10 Our meta-analysis evaluated the effect of reconstruction routes on mortality in five RCTs including 125 posterior mediastinal and 129 retrosternal cases, 19,[22][23][24][25][26] five case-control trials comprising 464 posterior mediastinal and 424 retrosternal cases, 18,19,30,33,35,36 and NCD analysis involving 3478 posterior mediastinal and 6308 retrosternal cases 7 (Figure 2C). Similar to NCD analysis, our meta-analysis revealed no significant difference in mortality between the posterior mediastinal and retrosternal groups (OR = 0.79, 95% CI: 0.56-1.12, p = 0.19).…”
Section: Mortalitymentioning
confidence: 99%
See 3 more Smart Citations